Free and unfree labour in the colonial Andes in the sixteenth and seventeenth centuries - Gil Montero, Raquel (2011)
This article analyses free and unfree labour in mining centres in the Andes during early Spanish colonial times. It focuses on two themes: the condition of indigenous or "native" people as "free labourers", and the mita system of unfree labour. For that purpose I shall consider the cases of Potosí, the most important mining centre in the Andes, and San Antonio del Nuevo Mundo in southern Bolivia, a large mine unaffected by the mita system of labour obligations.